Citrinin mycotoxin recognition and removal by naked magnetic nanoparticles. (15th July 2016) - Magro, Massimiliano; Moritz, Denise Esteves; Bonaiuto, Emanuela; Baratella, Davide; Terzo, Milo; Jakubec, Petr; Malina, Ondřej; Čépe, Klára; Aragao, Glaucia Maria Falcao de; Zboril, Radek; Vianello, Fabio
Highlights: Citrinin mycotoxin is produced during the fermentation process of Monascus mold. Naked magnetic nanoparticles are able of effectively bind citrinin. The complex between magnetic nanoparticles and citrinin was characterized. Naked magnetic nanoparticles are proposed for citrinin removal in foods. Abstract: Citrinin is a nephrotoxic mycotoxin which can be synthesized by Monascus mold during the fermentation process in foods. Monascus, generally described as red mold, is a red-pigmented filamentous fungus attracting a great interest for the production of natural dyes and cholesterol-lowering statins. We individuated a specie of Monascus producing high amount of natural dyes. However, this high pigmentation was correlated with the production of citrinin. Peculiar magnetic nanoparticles, synthesized in-house and called "Surface Active Maghemite Nanoparticles" (SAMNs), are proposed as an efficient and reliable mean for citrinin removal from Monascus treated foods. The nanomaterial efficiency for citrinin binding was proved on Monascus suspensions, and SAMN@citrinin complex was characterized by Mӧssbauer spectroscopy and magnetization measurements, showing that SAMNs resulted structurally and magnetically well conserved after citrinin binding. SAMNs are excellent and stable magnetic nano-carrier for toxin removal, which can be applied in food industry.